Promising role of Carob (Ceratonia siliqua L) phytochemical components against neurotoxicity induced by monosodium glutamate - Hassan IH El-Sayyad; Wafaa ME Elkholy; Wafaa A E Hamed (Global Journal of Zoology - Peertechz Publications, 2017)
The phytochemical constituents of Carob (Ceratonia siliqua L) showed therapeutic medical importance especially concerning neurotoxicity which represents the major public health problem. Neurodegenerative disorders are developed from different metabolic diseases and chemical component such as monosodium glutamate. It is the widely used chense sodium salt of the non-essential glutamic amino acid. It is one of the most popular fl avor enhancer. Monosodium glutamate is excitatory neurotransmitter in brain, increased the perception of wetness and saltiness as a taste sensation UMAMI. Treatment with the carob extract or their phytochemical constituents either protect or ameliorates these diseases which is promising.